1996
DOI: 10.1002/(sici)1097-4628(19960808)61:6<885::aid-app1>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characteristics of bagasse

Abstract: SYNOPSISBagasse is a solid waste that remains after crushing sugarcane. Since bagasse is used as a fuel in sugar mills, characterization of its thermal degradation is rather important in order to use it efficiently. Thermal analysis of bagasse was carried out using differential thermal analysis (DTA) and thermogravimetry (TG) under oxidizing and inert atmospheres. Kinetic studies were based on weight loss obtained from T G analysis. Thermal degradation of bagasse takes place in two stages: volatilization and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 0 publications
2
33
0
1
Order By: Relevance
“…The impact of an oxidative environment versus that of an inert atmosphere upon bagasse pyrolysis was investigated by several research groups [303,387,392,393]. In each case, there was an increase in apparent activation energy when the inert (N 2 ) atmosphere was replaced with an oxidative environment.…”
Section: Analysis Of Published Kinetic Data For Sugarcane Bagasse Pyrmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of an oxidative environment versus that of an inert atmosphere upon bagasse pyrolysis was investigated by several research groups [303,387,392,393]. In each case, there was an increase in apparent activation energy when the inert (N 2 ) atmosphere was replaced with an oxidative environment.…”
Section: Analysis Of Published Kinetic Data For Sugarcane Bagasse Pyrmentioning
confidence: 99%
“…Excluding the extraordinary 1429% increase in E given by Roque-Diaz et al [303], the average increase in E a on the basis of five studies by these four groups was 47% with a standard deviation of 17%. Nassar [298,385,392] conducted his bagasse pyrolysis experiments under two different types of inert atmosphere (N 2 and He). The E a values recorded for pyrolysis under nitrogen were 87.9 kJ mol −1 and 46.7 kJ mol −1 for the low and high temperature regions, respectively, while the corresponding E a values obtained for pyrolysis under helium were 118.1 kJ mol −1 and 69.1 kJ mol −1 , respectively.…”
Section: Analysis Of Published Kinetic Data For Sugarcane Bagasse Pyrmentioning
confidence: 99%
“…Apart from the kinetic studies at the bench scale [18][19][20][21], different technologies have been applied, such as fixed bed reactor [22,23,4], vacuum pyrolyzer [24,25] and rotary drum [22]. According to Bridgwater [26], fluidized beds are the most popular configurations owing to their ease of operation and scale-up.…”
Section: Introductionmentioning
confidence: 99%
“…The last two components represent small fraction of the total weight [27] . The weight loss percent and the rate of loss (da=dt) (differential thermogravimetery) of cane bagasse fibers against temperature increment is shown in Fig.…”
Section: Thermal Decomposition Of Sugar Cane Bagassementioning
confidence: 99%
“…Developments of wood flour reinforced composite of a high temperature engineering polymer (polyphenylene ether) with the aid of low molecular weight thermosetting liquid bifunctional epoxy (EPON 828) is very important due to its popularity in automotive industry [26] . Thermal degradation of sugar bagasse using TGA indicates two degradation steps, volatilization and decarbonization; the activation energy for the first is higher than the second [27] . Recent study [6] using TGA technique showed that bagasse fibers treated with silane and grafted with polystyrene and divinyl benzene remarkably increase its hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%